Professionalizing schools on self-regulated learning: roles, responsibilities and challenges of process coaches - Backers, Lies; Van Keer, Hilde (Frontiers in Education, 2025)
The implementation of self-regulated learning (SRL) in primary and secondary schools is complex and requires a sustainable long-term development of the complete school. To support school leaders and their school team to implement SRL, a two-year school-wide professionalization trajectory was designed in collaboration with an in-service teacher professionalization organization. School leaders participated in a professional learning community (PLC) and were guided by process coaches from the in-service teacher professionalization organization. This study focuses on these coaches and more specific on (1) their roles and responsibilities and (2) the challenges they face in guiding SRL-focused professionalization programs. Bi-monthly focus group discussions with the process coaches were executed to gain more insight in their perspectives. In total, nine focus group discussions were organized, and thematic analysis was used to examine the qualitative data collected during these. Four roles for the process coaches could be identified throughout the two-year professionalization trajectory, namely the roles of a coach, an expert, a coordinator, and a learner. In these roles, the process coaches experienced various challenges and tensions. For example, they faced challenges in defining their role as either a content expert or a facilitator of group learning. Furthermore, the results indicate that challenges were also experienced at other levels, such as within the organization of the PLC, dealing with the diversity among participating school leaders, and involving the school team when implementing SRL school-wide.